Rectal Carcinoma with Heterotopic Bone: Report of a Case - Yuichi Nagao; Shohei Shimajiri; Takefumi Katsuki; Yoshifumi Nakayama; Koji Yamaguchi (Case Reports in Gastroenterology, 2010)
Heterotopic bone is rarely present in malignant tumors of the gastrointestinal tract. We herein report a case of rectal adenocarcinoma with heterotopic bone. A 46-year-old Japanese male presented to our hospital with abdominal distension and constipation. Colonoscopic examination showed an ulcerated polypoid tumor of the rectum which nearly obstructed the rectal lumen. Abdominal computed tomography showed a tumor of the rectum with calcified deposits. Low anterior resection with lateral lymph node dissection was performed under the tentative diagnosis of rectal cancer. Histological examination of the resected specimen showed mucinous carcinoma of the rectum with heterotopic bone. One of the metastatic lymph nodes dissected also showed heterotopic bone. In the present report, we describe this rare tumor and briefly review the pertinent literature regarding rectal cancer with heterotopic bone.